Tailoring Electromagnetic Interference Shielding Performance of Conductive Nanocomposite Coating Using Textile Substrates. Issue 24 (14th November 2021) - Duan, Minghan; Hou, Yijie; Guo, Min; Li, Xiangpeng; Li, Xian; Wang, Jilong; Ma, Ying
Abstract: Textile‐substrate electromagnetic interference (EMI) shielding materials show great promise for next‐generation electronic communication technology challenges. A new strategy based on structure optimization is highly desired for wearable electronic devices to improve EMI shielding performance. Here, the enhancement effect of fabric structure on the shielding effectiveness (SE) of conductive nanocomposite coating is demonstrated. Plain fabrics with different fabric densities are weaved and used as the substrate to be layer‐by‐layer assembled by graphite oxide and polypyrrole. The resulting conductive nanocomposite coating endows common cotton fabrics with electrical conductivity and EMI shielding ability. In comparison, the EMI SE of the conductive coated fabrics is depended on the fabric density, that is, the pore size. Specifically, the EMI SE of the coated fabric can be increased by ≈71% through the control of fabric structure. Interestingly, the EMI SE is always the maximum at the fabric density of 100 × 100 picks/ 10 cm,  different from the electrical conductivity. Moreover, the sueding treatment was proven to be useful to further improve the EMI SE of the conductive coated fabrics. This work presents the significance of substrate structures in EMI shielding, offering new opportunities for the development of high efficiency EMI shielding fabrics. Abstract : This work presents the enhancement effect of fabric structure on electromagnetic interference (EMI) shielding performance of conductive nanocomposite coatings, offering a new opportunity for the development of high‐efficiency EMI shielding materials. The existence of crucial structure parameters for EMI shielding has been demonstrated, due to the fact that the maximum EMI shielding effectiveness (SE) of different coatings maintained at a certain fabric density.